Pelecehan Verbal Sebagai Kekerasan Berbasis Gender Di Ruang Siber Pelajaran Dari Perkara Baiq Nuril - Trisnayanti, Ni Komang Kumala; Wulandari, Ni Gusti Agung Ayu Mas Tri (Consensus : Jurnal Ilmu Hukum, 2025)
Verbal abuse in cyberspace is a form of online gender-based violence that is increasingly experienced by women, especially in Indonesia. This is related to the development of digital technology. The case of Baiq Nuril is a clear reflection of the problems of criminal law in Indonesia, particularly in the context of protecting victims of sexual violence and the implementation of the Electronic Information and Transactions Law (ITE Law). Baiq Nuril, a victim of verbal abuse by her superior, was criminalized under Article 27 paragraph (1) of the ITE Law after she recorded obscene conversations as a form of self-protection. This study uses a normative juridical approach by analyzing relevant legal instruments and their application in the Baiq Nuril case. The results of the study show that verbal harassment in cyberspace must be understood as gender-based violence that requires special legal protection, not just online communication ethics. The Baiq Nuril case is a real example of a legal framework that is not gender-sensitive and has the potential to cause problems. This relates to the application of criminal law and the criminalization of victims. In conclusion, this case provides an important lesson about the urgency of regulatory reform and the strengthening of amicus curiae, in order to achieve more responsive justice.